TopVenues: An Executable Corpus and Research Tool for Cybersecurity Literature Reviews - Barbieri, Sidnei; Ferraz, Ágney Lopes Roth; Pereira Júnior, Lourenço Alves (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg); 2026: Anais Estendidos do XXVI Simpósio Brasileiro de Cibersegurança, 2026)
Cybersecurity literature reviews depend on a stable denominator: the papers eligible for screening before synthesis begins. In practice, researchers reconstruct this denominator from changing portals, APIs, and exports, making the resulting corpus difficult to audit or reuse. TopVenues makes corpus construction an executable research artifact. Given a declared venue and year scope, it normalizes DBLP metadata, enriches records with abstracts and BibTeX, and materializes a monotonic SQLite snapshot exposed through a command-line interface, a web application, ranked search, and review-oriented exports. The release declares its venue policy, distinguishes bibliographic records from abstract-enriched records, and records field-level provenance. A reviewer can verify a pinned snapshot offline, exercise ranked search and exports, and reproduce the snapshot-bound workflows included with the release. The tool therefore provides both a usable literature workbench and a fixed, inspectable population for cybersecurity measurement.